Introduction to the Special Issue: Public and Private Labor Standards Policy in the Global Economy. (25th May 2017) - Fransen, Luc; Burgoon, Brian
Abstract: This article introduces a Global Policy Special Issue on public and private protections of labor and social standards in the global economy, exploring whether public and private regulations of such standards develop in harmony or tension with one another. It promotes an approach to studying public‐private interactions in global labor governance that is sensitive to how interactions are important at different stages in the making of public and private regulation; how the causal interaction can go from the public to the private and from the private to the public; how such interaction varies in quality and promise across different parts of the world, labor issue areas and policy instruments; and how public‐private interaction can only be captured by combining case histories with large‐N analysis. The evidence from the Special Issue's articles leads to a set of generic propositions, describing how public interventions tend to strengthen private labor policy, while private interventions tend to either modestly substitute for or have little effect upon public labor and social protections. The article then discusses how these dynamics may be influenced by the political contentiousness of the specific labor issue and the characteristics of the state. Abstract : The fostering of equity in global economic life requires continued research into how public and private policies can undergird and undermine one another, work together and at cross purposes, in the protection of labor and social standards that are increasingly at the center of global politics.